Vivir en tiempos de odio Concha Castroviejo y la ficcionalización del malestar femenino en Víspera del odio (1958) - Cerullo, Luca (L’art de vivre, de survivre, de revivre. Approches littéraires. Le 50e anniversaire des études romanes à l’Université de Łódź, 2022)
The purpose of this paper is to analyse the novel Vispera del odio (1958), byConcha Castroviejo, with special focus on its impact as a literary testimony of the femalecondition during the Francoist years. The central plot in the novel revolves around anunhappy marriage, with the wife experiencing violence from her husband. The dramaticsituation became a common element in many novels written by women of that time,hence the paradigmatic value of a general condition of feminine struggle that definesa consequent attitude and ability of surviving to adverse historical and social circumstances.